INFUTPEDIA: Media Pembelajaran Berbasis Android dengan Pendekatan STEAM (Science, Technology, Engineering, Art, and Mathematics) Sebagai Alternatif Pemecahan Masalah di Indonesia - Rodiana, Sofia Oka (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Indonesia's digital education ecosystem has very diverse control rooms. Several scenarios or strategies must be used to be implemented during the transformation of digital education after the COVID-19 pandemic. The existence of the COVID-19 pandemic for more than two years has provided space for teachers to carry out innovations, especially digital innovations. One of the results of innovations that have been successfully utilized to date is learning media. From the various learning activities carried out, there are various approaches used by teachers so that learning can be understood by students and is more meaningful, such as science, technology, engineering, art, and mathematics (STEAM) approaches to solve problems. In this study, the Research and Development (R&D) method was used. Learning based on the STEAM approach aims to increase students' understanding and knowledge of mathematics, science, and technology. As for the art elements, it is hoped that students will be accustomed to solving a problem in a creative way.In order to improve student skills, creativity and sensitivity to environment, the INFUTPEDIA (Indonesia for Future) innovation is here. INFUTPEDIA is an Android-based learning media with the STEAM approach as an alternative or solution to solving problems in Indonesia. Learning steps with the STEAM approach include: find identify problems and solutions, envision products, plan products, and manufacture and test products. So that this project-based exercise will train students to be able to solve problems and make decisions for the progress of Indonesia.